An efficient route to the synthesis of novel zwitterionic pyridinium-cyanopropenides with 3-heteroaryl-substituted trimethinium salts. Issue 25 (30th May 2022) - Samani, Ziba Rafiee; Mehranpour, Abdolmohammad
Abstract : Synthesis of new zwitterionic derivatives via the reaction of 2-substituted 1, 3-bis(dimethylamino)-trimethinium salts with malononitrile or ethyl cyanoacetate in the presence of Et3 N in ethanol at reflux. Abstract : In this study, eight new zwitterionic derivatives were synthesized using a simple design method from the reaction of various 2-substituted 1, 3-bis(dimethylamino)-trimethinium salts with malononitrile or ethyl 2-cyanoacetate in excellent yields in the presence of triethylamine in ethanol at reflux. The molecular structures of the new compounds were confirmed by IR, UV/vis, mass, 1 H, and 13 C NMR spectra as well as by elemental analyses.